Mesenchymal Stem Cells - Isolation, Characterization and Applications 2017
DOI: 10.5772/intechopen.68176
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Therapies for Osteoarthritis: From Pre-Clinical to Clinical Applications

Abstract: Although many surgical and pharmaceutical interventions are currently available for treating osteoarthritis (OA), restoration of normal cartilage function remains inefficient.In fact, because of the absence of vasculature within the articular cartilage (AC), the selfpotential for regeneration is very poor. Recently, researchers and clinicians have been focusing on alternative methods for cartilage preservation and repair. It has been shown that AC contains a population of stem cells or progenitor cells, simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have been investigated for use in cell-based therapy for early OA in pre-clinical and clinical treatments [14,15]. A pilot study using autologous bone marrow-derived mesenchymal stem cells on knee OA has shown promising results [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have been investigated for use in cell-based therapy for early OA in pre-clinical and clinical treatments [14,15]. A pilot study using autologous bone marrow-derived mesenchymal stem cells on knee OA has shown promising results [16].…”
Section: Introductionmentioning
confidence: 99%